-4x-x=

Simple and best practice solution for -4x-x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x-x= equation:


Simplifying
-4x + -1x = 0

Combine like terms: -4x + -1x = -5x
-5x = 0

Solving
-5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-5'.
x = 0

Simplifying
x = 0

See similar equations:

| 14.4y-5.1=2.1 | | 3x^7+15x^6+18x^5= | | 2w^2+w-10=0 | | 4y+y(2+3y)= | | 9(2-1j)+3(5+2j)=2(7-2j)-4(1j-1) | | 3(x+88)= | | 2g+14=-8 | | -4y=6-6x | | 4p-(3p+2r-4)+3-r= | | 4s^2+3s-15=0 | | 17=3 | | 10x-3x+(-5x)= | | 15+5x=5(x+3) | | 8+c=13 | | 4p-(3p+2r-4)= | | 9x^8-72x^6=0 | | v-7=-12 | | 20x-24y=120 | | -4y+2x+8=0 | | x=100-3x | | x-14=-32 | | 0.05x+1.02x= | | 3-2*=11 | | 7+3x=3x+10 | | 19+b=17 | | -q-11=2+4 | | x^4+-15x^2+56=0 | | 2x-3=4x-2 | | 2j+5=6h | | 6a-4a=-36 | | (7x)-(2x)= | | 81=-3(-6+3n) |

Equations solver categories